Perfil sociodemográfico de usuários de um centro de atenção psicossocial e o trabalho. - Passos de Oliveira, Ana Carolina; Pereira Jorge, Iranise Moro; Mariotti, Milton Carlos (Brazilian Journal of Occupational Therapy / Cadernos Brasileiros de Terapia Ocupacional, 2017)
Introduction: Currently the work occupies a central position in the life of the adult individuals, being this activity responsible for the provision of income, social relations and personal satisfaction. The population in general and in particular some individuals with mental disorders, end up limited and even deprived regarding to access to this activity. The main meaning of the work ends up failing, being the individual subjected to the needs of capital and not its personal needs. Objective: The objective of this study was to outline the sociodemographic profile of users of a Psychosocial Care Center II with a focus on work history. The occupational profile may contribute to the planning of Work Generation and Income workshops. Method: It is configured as a quantitative, descriptive cross-sectional study. A semi-structured questionnaire was used to collect data and data analysis was performed through descriptive statistics using the Statistical Package for the Social Sciences (SPSS) program, with the recombination of the literature data. Results: It was found that the great majority of the users interviewed are far from work and have previous experience in agricultural activities, especially in the care of vegetable gardens. Conclusion: The development of workshops to generate work and income can make it possible to resume the work activity of these individuals and the occupational therapist through their professional skills can contribute to this process.